KEEFEKTIFAN KONSELING KELOMPOK REALITA UNTUK MENINGKATKAN PEMAHAMAN IDENTITAS DIRI SISWA SEKOLAH MENENGAH PERTAMA - Maslikan Maslikan (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2018)
This study aims to test the effectiveness of reality counseling to improve students' self-identity in junior high. This research uses pre experimental with pretest-posttest one group design. The data analysis used is paired test of T-test. To see the change of self-understanding level in the experimental group between pretest and posttest by looking at the price of ttable on the degrees of freedom (dk), ie the amount is N-1, and at a significant level Î± = 0.05 (95%) then obtained ttable = 1.771, assuming if thitung > ttabel then Ha